Coupling coefficient range extension technique for broadband branch-line coupler. Issue 1 (2nd January 2018) - Qamar, Zeeshan; Zheng, S.Y.; Chan, W.S.; Ho, Derek
Abstract: In a conventional branch-line coupler (BLC), high coupling coefficients require very narrow lines, which results in high fabrication complexity and reduction in power handling capacity. In addition, changes in multiple design parameters are required to realize arbitrary coupling coefficients. In this paper, we present the design, fabrication, and characterization of a novel broadband branch-line coupler that extends the range of arbitrary coupling coefficients. The proposed structure is also able to achieve different coupling through tuning only one design parameter, and therefore can be used as a tunable coupler. Closed-form design equations are presented for the synthesis of broadband BLCs based on the proposed structure. To validate the proposed structure and the corresponding design methodology, a variety of broadband BLCs with different coupling coefficients have been designed, fabricated, and measured. Measurements show that couplers with 6, 9, and 12 dB coupling coefficients provide wide fractional bandwidths of 49, 49, and 52%, respectively.